2005
DOI: 10.1167/iovs.04-1174
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Retinal Nerve Fiber Thickness Measurements Using the Stratus OCT in Normal and Glaucomatous Eyes

Abstract: Reproducibility of RNFL measurements using the Stratus OCT is excellent in normal and glaucomatous eyes. The nasal quadrant appears to be the most variable measurement. Standard RNFL and Fast RNFL scans are equally reproducible and yield comparable measurements. These findings have implications for the diagnosis of glaucoma and glaucomatous progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
193
2
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(223 citation statements)
references
References 15 publications
25
193
2
3
Order By: Relevance
“…With evolution of technology, the accuracy of OCT has significantly improved and RNFL measurement with OCT is considered one of the most reliable methods to estimate the severity of glaucoma patients to date. 12,13 We utilized the same method to investigate the RNFL thickness of RP patients.…”
Section: Discussionmentioning
confidence: 99%
“…With evolution of technology, the accuracy of OCT has significantly improved and RNFL measurement with OCT is considered one of the most reliable methods to estimate the severity of glaucoma patients to date. 12,13 We utilized the same method to investigate the RNFL thickness of RP patients.…”
Section: Discussionmentioning
confidence: 99%
“…These instruments have been shown to provide measurements of the RNFL thickness with good repeatability and reproducibility, which are mandatory requisites for accurately assessing a disease and its progression. [7][8][9] Moreover, their measurements have been shown to correlate positively with ex vivo histological measurements of the retina. 10,11 Spectral-domain OCT (SD-OCT) has now replaced TD-OCT and a large number of instruments by different manufacturers are commercially available.…”
Section: Introductionmentioning
confidence: 88%
“…Time-domain OCT provides reproducible RNFLT measurements around the ONH. 14 In this report, SLP-VCC and SLP-ECC imaging modalities are referred to as VCC and ECC respectively, whereas time-domain OCT is referred to as OCT. Previous longitudinal studies have shown that VCC, ECC, and OCT can provide good discrimination in rates of RNFLT change between progressing and non-progressing glaucoma patients determined by visual field changes and/or expertassessed stereophotograph change.…”
Section: Introductionmentioning
confidence: 99%